Restoration of HCV-specific CD8+ T cell function by interferon-free therapy - Martin, Bianca; Hennecke, Nadine; Lohmann, Volker; Kayser, Antonin; Neumann-Haefelin, Christoph; Kukolj, George; Böcher, Wulf-Otto; Thimme, Robert (Journal of hepatology, 2014)
Background & Aims - Chronic hepatitis C virus (HCV) infection is characterised by a failure of virus-specific CD8+ T cells that is mainly caused by viral escape and T cell exhaustion. Constant antigen stimulation has been suggested to contribute to HCV-specific CD8+ T cell exhaustion. However, IFN-based therapies failed to recover HCV-specific CD8+ T cell function suggesting that the damage to CD8+ T cells may be permanent even after antigen removal. It was therefore the objective of this study to analyse the impact of inhibition of ongoing viral replication by IFN-free therapy with direct acting antivirals (DAA) on the phenotype and function of HCV-specific CD8+ T cells. - Methods - Virus-specific CD8+ T cells obtained from a patient cohort of 51 previously untreated chronically infected patients undergoing IFN-free therapy with a combination of faldaprevir (a protease inhibitor) and deleobuvir (a non-nucleoside polymerase inhibitor) with or without ribavirin were analysed ex vivo and after in vitro expansion at baseline, wk4, wk12, and after treatment. - Results - Our results show the rapid restoration of proliferative HCV-specific CD8+ T cells in the majority of patients with SVR12 within 4weeks of therapy suggesting that IFN-free therapy mediated antigen removal may restore CD8+ T cell function. - Conclusions - This study indicates a specific restoration of proliferative HCV-specific CD8+ T cells under IFN-free therapy. This is in contrast to PegIFN-based therapies that have been shown not to restore T cell function during and after chronic infection.